Landasan Filsafat Toleransi Beragama sebagai Pilar Kerukunan Sosial: Studi Kasus Desa Ngrimbi, Kecamatan Bareng, Kabupaten Jombang: Landasan Filosofis Toleransi Beragama sebagai Pilar Kerukunan Sosial: Studi Kasus Desa Ngrimbi, Kecamatan Bareng, Kabupaten Jombang - Andi Setyo Pambudi (DIALEKTIKA, 2026)
Indonesia is a nation marked by religious diversity, making tolerance a vital pillar for maintaining social harmony. However, most previous studies have focused on normative aspects or macro-level policies, while empirical explorations of tolerance at the village level remain limited. This research addresses the gap by examining Ngrimbi Village, Bareng District, Jombang Regency, as a case study of how the philosophy of religious tolerance can be transformed into concrete practices of communal harmony. Employing a qualitative single-case study design, data were collected through participant observation, in-depth interviews, focus group discussions, and document analysis, and analyzed using an interactive model with triangulation of sources and methods. The findings reveal that tolerance in Ngrimbi is manifested in interfaith social solidarity, mutual participation in religious celebrations, collective labor activities, and the active roles of religious leaders and local government. Multicultural education in schools, Javanese cultural values such as tepa selira and rukun agawe santosa, and youth engagement further reinforce intergenerational tolerance. Nevertheless, challenges such as exposure to intolerant digital content and potential disputes over the use of worship spaces persist. The study recommends strengthening interfaith village forums, promoting digital literacy, and integrating multicultural curricula to develop an “active tolerance” model that can be replicated in other communities.